(untitled) (Praxis Educativa, 2017)
The present work intends to analyze the current educational advisor’s insertion in the Brazilian contemporary education, noting its relation with the construction of democratic management and improves the quality of public schools in Brazil. We intend to demonstrate, through reading and criticism of the legislation and relevant literature that the action of the educational advisor can (and every day it becomes more obvious that) to help students exercise in a critical way their citizenship.